Stress among Italian male and female patrol police officers: a quali-quantitative survey. Issue 4 (11th November 2014) - Acquadro Maran, Daniela; Varetto, Antonella; Zedda, Massimo; Franscini, Monica
Abstract : Purpose: – The purpose of this paper is to carry out a quali-quantitative study to analyze unease and perceived stress in a population of 485 male and female police officers in a large city in northern Italy, and investigate the consequences of these and the coping strategies adopted. The working context the paper chose to investigate was the Municipal Police, which is characterized by strong links with the local community. As suggested in the literature, the paper focalized the attention both on organizational and operational stressors. Design/methodology/approach: – Quali-quantitative study: a self-administered questionnaire. Findings: – Results show that both men and women are self-critical and their evaluation of the professional and contextual circumstances in which they operate is filtered by pessimism and self-blame, with higher levels of somatization in women: female patrol police officers are at the highest risk of psychological distress. Originality/value: – This is, to the best of the knowledge, the first quali-quantities study in Italy to consider the gender variable within a single police force.